2013
DOI: 10.1371/journal.pone.0064866
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antineoplastic Drugs in a Male Spontaneous Mammary Tumor Model

Abstract: Male breast cancer is a rare disease. The limited number of clinical cases has led to the primary treatments for men being derived from female breast cancer studies. Here the transgenic strain FVB/N-Tg(MMTV-PyVT)634Mul/J (also known as PyVT) was used as a model system for measuring tumor burden and drug sensitivity of the antineoplastic drugs tamoxifen, cisplatin, and paclitaxel on tumorigenesis at an early stage of mammary carcinoma development in a male mouse model. Cisplatin treatment significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…40 The antiapoptotic effect of survivin is connected with caspase-3 activation. 41 Survivin can directly inhibit the activity of caspase-3 downstream of the apoptotic pathway and indirectly inhibit the activation of caspase-3 by means of caspase-9. The homodimers of Bax could be increased on account of Bax strongly expressing; furthermore, Bax overexpression could alter mitochondrial transmembrane potential, activate caspase-7 and caspase-3 downstream, accomplish substrate excision, and accelerate apoptosis by combining with mitochondrial membrane, as well as initiating a cascade of caspase.…”
Section: Discussionmentioning
confidence: 99%
“…40 The antiapoptotic effect of survivin is connected with caspase-3 activation. 41 Survivin can directly inhibit the activity of caspase-3 downstream of the apoptotic pathway and indirectly inhibit the activation of caspase-3 by means of caspase-9. The homodimers of Bax could be increased on account of Bax strongly expressing; furthermore, Bax overexpression could alter mitochondrial transmembrane potential, activate caspase-7 and caspase-3 downstream, accomplish substrate excision, and accelerate apoptosis by combining with mitochondrial membrane, as well as initiating a cascade of caspase.…”
Section: Discussionmentioning
confidence: 99%
“…BC is a rare disease in men. It has been reported that 1% of BC diagnosed in the United State is found in men [30][31][32]. In the present study, the patients were subsequently divided into thirteen groups of age as follows: 29 to…”
Section: Sex and Age At Diagnosismentioning
confidence: 99%